Parents' Experiences of Limiting Family Size After Birth Trauma: a Hermeneutic Phenomenological Study - O'Byrne, Sofia (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2025)
Background: Pregnancy and childbirth is a profound and life-changing time for women and their families. Although it can be a positive and empowering experience, for some it can be a traumatic event. Birth trauma can have severe impacts on a woman's mental health, on the family unit, and on future reproductive decisions. After a traumatic birth experience, some women alter their future birth plans, for example by opting for an elective caesarean section or planning a homebirth. However, there are those who are so traumatised that they choose to forgo future pregnancy and birth altogether, even if they badly desire another child. Aims and Objectives: The aim of this study is to develop an in-depth understanding of the lived experience of limiting family size to less than desired as a result of birth-related trauma. In order to provide meaning to this aim, specific objectives were identified; to gather rich descriptions of the lived experience of parents' who have chosen not to have more children as a result of birth-related trauma, and to uncover meaning in these experiences through hermeneutic analysis. Methodology : This study utilised a hermeneutic phenomenological approach underpinned by the philosophy of Heidegger and Gadamer. Data Collection: In-depth interviews were used to collect data. They were conducted both in-person and online. Recruitment: Participants were recruited from a separate longitudinal study. Purposeful sampling was used to recruitment women who had limited their family size as a result of a traumatic birth experience. Women's partners were also invited to participate. Sample: The sample included 15 women who had experienced a birth or birth-related event they identified as traumatic, along with 4 men who were their partners. Data Analysis: Hermeneutic analysis was conducted using the Dibley et al.'s (2020) guidance for iterative interpretive analysis. Findings: The findings are presented through three passages, eight emerging themes, and one constitutive pattern. Passage one, 'Confronting a Difficult Decision' consists of three emerging themes: `Instinctive Knowing', `Eliminating Risk', and `Preventing Mental Anguish'. Passage two, 'Bearing the Burden in the Aftermath', consists of emerging themes 'Navigating Emotional Turmoil', and `Enduring Unfulfilled Expectations'. Passage three, `Moving Forward, But Not Moving On', consists of emerging themes 'Reaching Acceptance', 'Lingering Trauma', and 'Making it Permanent'. The three passages and eight emerging themes are interconnected together through the constitutive pattern, 'Acting on Self-Preservation'. Conclusions: This study offers the first qualitative exploration of the link between birth trauma and decisions to limit family size. Key findings highlight a crucial distinction between minimising and eliminating the risk of subsequent birth trauma, the development of mistrust in maternity services, and the role of modifiable versus non-modifiable contributors to trauma. These insights deepen our understanding of the lasting impact of traumatic births on reproductive decision-making.
APPROVED
Keywords: Midwifery; Midwife; Birth Trauma; Traumatic Birth; Birth-related trauma; Perinatal Mental Health; Family Planning; Maternity Care